Gaya Kepemimpinan Transformasional Parabela dalam Pengembangan Pariwisata Di Kabupaten Buton - Zainul Abidin; Syahrul Hidayat (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2021)
Traditional leadership is not only passive and only implementers of customs but can also be a developer of community culture into a commodity. Parabelle leadership as a traditional leader can be a driver of tourism development. This study aims to analyze the transformational leadership style of parebela in tourism development in Buton Regency. This study seeks to explore and understand the parabellar leadership style so that descriptive qualitative research is suitable for use. Descriptive in the sense of writing, speech and behavior of the observed party. The strategy used is a case study, chosen because the research question is related to how parable leadership style is. Sources of data obtained through interviews, documents, and direct observation. The interactive model data analysis used consisted of data reduction to verification. The results show that the parabelle leadership style has two characteristics, namely having an ideal influence and being able to provide inspirational motivation for tourism development. Parabela can be categorized as meeting the transformational leadership style. The involvement of parabels needs to be increased because the role of parabels in the community is very effective.